DEVELOPMENT OF MATHEMATICAL DERIVATIVE BOARD PROPS TO IMPROVE STUDENTS' MATHEMATICAL CONCEPT UNDERSTANDING - Elmania, Putri; Syahirani, Siti; Safitri, Ayu; Lubis, M. Ilyas; Arianto, Arianto (Universitas Labuhanbatu, 2024)
The feasibility results were obtained based on the results of the validation questionnaire for the mathematics derivative board props for each validator, namely media experts, who obtained a percentage result of 78.24% in the